Bias and Precision in Magnetic Resonance Imaging‐Based Estimates of Renal Blood Flow: Assessment by Triangulation - Alhummiany, Bashair A.; Shelley, David; Saysell, Margaret; Olaru, Maria‐Alexandra; Kühn, Bernd; Buckley, David L.; Bailey, Julie; Wroe, Kelly; Coupland, Cherry; Mansfield, Michael W.; Sourbron, Steven P.; Sharma, Kanishka (Journal of magnetic resonance imaging, 2022)
Background Renal blood flow (RBF) can be measured with dynamic contrast enhanced‐MRI (DCE‐MRI) and arterial spin labeling (ASL). Unfortunately, individual estimates from both methods vary and reference‐standard methods are not available. A potential solution is to include a third, arbitrating MRI method in the comparison. Purpose To compare RBF estimates between ASL, DCE, and phase contrast (PC)‐MRI. Study Type Prospective. Population Twenty‐five patients with type‐2 diabetes (36% female) and five healthy volunteers (HV, 80% female). Field Strength/Sequences A 3 T; gradient‐echo 2D‐DCE, pseudo‐continuous ASL (pCASL) and cine 2D‐PC. Assessment ASL, DCE, and PC were acquired once in all patients. ASL and PC were acquired four times in each HV. RBF was estimated and split‐RBF was derived as (right kidney RBF)/total RBF. Repeatability error (RE) was calculated for each HV, RE = 1.96 × SD, where SD is the standard deviation of repeat scans. Statistical Tests Paired t‐tests and one‐way analysis of variance (ANOVA) were used for statistical analysis. The 95% confidence interval (CI) for difference between ASL/PC and DCE/PC was assessed using two‐sample F‐test for variances. Statistical significance level was P < 0.05. Influential outliers were assessed with Cook's distance (Di > 1) and results with outliers removed were presented. Results In patients, the mean RBF (mL/min/1.73m2) was 618 ± 62 (PC), 526 ± 91 (ASL), and 569 ± 110 (DCE). Differences between measurements were not significant (P = 0.28). Intrasubject agreement was poor for RBF with limits‐of‐agreement (mL/min/1.73m2) [−687, 772] DCE‐ASL, [−482, 580] PC‐DCE, and [−277, 460] PC‐ASL. The difference PC‐ASL was significantly smaller than PC‐DCE, but this was driven by a single‐DCE outlier (P = 0.31, after removing outlier). The difference in split‐RBF was comparatively small. In HVs, mean RE (±95% CI; mL/min/1.73 m2) was significantly smaller for PC (79 ± 41) than for ASL (241 ± 85). Conclusions ASL, DCE, and PC RBF show poor agreement in individual subjects but agree well on average. Triangulation with PC suggests that the accuracy of ASL and DCE is comparable. Evidence Level 2 Technical Efficacy Stage 2